2023
DOI: 10.1371/journal.pgph.0001136
|View full text |Cite
|
Sign up to set email alerts
|

Drought, armed conflict and population mortality in Somalia, 2014–2018: A statistical analysis

Abstract: During 2010–2012, extreme food insecurity and famine in Somalia were estimated to account for 256,000 deaths. Since 2014 Somalia has experienced recurrent below-average rainfall, with consecutive failed rains in late 2016 and 2017 leading to large-scale drought, displacement and epidemics. We wished to estimate mortality across Somalia from 2014 to 2018, and measure the excess death toll attributable to the 2017–2018 drought-triggered crisis. We used a statistical approach akin to small-area estimation, and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During a famine in Somalia (2010 to 2012), the method found that CDR increased about fivefold to eightfold, with some 260,000 excess deaths ( 22 ), while in South Sudan we estimated 380,000 excess deaths, about 1.7 times the counterfactual ( 23 ). Repeat Somalia studies suggested about 45,000 excess deaths during the 2016 to 2018 drought ( 24 ) and a similar amount during the first year of the ongoing drought ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…During a famine in Somalia (2010 to 2012), the method found that CDR increased about fivefold to eightfold, with some 260,000 excess deaths ( 22 ), while in South Sudan we estimated 380,000 excess deaths, about 1.7 times the counterfactual ( 23 ). Repeat Somalia studies suggested about 45,000 excess deaths during the 2016 to 2018 drought ( 24 ) and a similar amount during the first year of the ongoing drought ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The country’s fragile and fragmented health system, unclear governance structure, and limited health financing hampers the routine access and delivery of essential vaccines [ 7 ]. The recurrent humanitarian health emergencies afflicting the country every four to five years further weaken the system by adding to the caseload of vector- and water-borne diseases and severe malnutrition of already vulnerable populations [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged dry spells significantly contribute to this crisis [14], yet it is crucial to recognize that droughts are not the sole driver. Various factors, including hydrological conditions, food production capabilities, market access, insufficient humanitarian aid, conflicts, and displacement, contribute to the complex challenges households face [13,2,19,3,24]. Studying food security in this context is intricate, involving multiple variables, scales, and non-linear relationships, making it unsuitable for predictive machine learning [25,26].…”
Section: Introductionmentioning
confidence: 99%